2013
DOI: 10.1155/2013/760208
|View full text |Cite
|
Sign up to set email alerts
|

The Human Urinary Proteome Fingerprint Database UPdb

Abstract: The use of human urine as a diagnostic tool has many advantages, such as ease of sample acquisition and noninvasiveness. However, the discovery of novel biomarkers, as well as biomarker patterns, in urine is hindered mainly by a lack of comparable datasets. To fill this gap, we assembled a new urinary fingerprint database. Here, we report the establishment of a human urinary proteomic fingerprint database using urine from 200 individuals analysed by SELDI-TOF (surface enhanced laser desorption ionisation-time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…Specialized scientific databases greatly help to facilitate this process [76]. In the field of nephrology, omics databases include "the Kidney and Urinary Pathway Knowledge Base" [77], the "Human Urinary Proteome Fingerprint Database" [78], and the "Chronic Kidney Disease database" [79]. More recently, a publicly available database platform that solely collects peptidomic and proteomic datasets manually extracted from published studies relative to CKD has been set up [80].…”
Section: Discussionmentioning
confidence: 99%
“…Specialized scientific databases greatly help to facilitate this process [76]. In the field of nephrology, omics databases include "the Kidney and Urinary Pathway Knowledge Base" [77], the "Human Urinary Proteome Fingerprint Database" [78], and the "Chronic Kidney Disease database" [79]. More recently, a publicly available database platform that solely collects peptidomic and proteomic datasets manually extracted from published studies relative to CKD has been set up [80].…”
Section: Discussionmentioning
confidence: 99%
“…In the same framework we also cover an assorted disease profiling database valuable for subtractive disease analysis studies, the Large-Scale Screening Resource (LSSR) that contains 81,980 entries, referring to 13,589 molecules. Moreover, a peak profiling database for biomarker patterns research, the Urinary Peptidomics and Peak-maps (UPdb) [63] database that comprises Human urinary fingerprints from 200 subjects analysed mainly through surface enhanced laser desorption ionisation-time of flight mass spectrometry (SELDI-TOF-MS).…”
Section: Disease Profiling Databasesmentioning
confidence: 99%
“…Inclusion criteria were peptidomics or proteomics case-control studies relative to CKD and only studies that examined human specimens. In addition to the literature search, the authors queried several databases including the 'Chronic Kidney Disease database' [7], 'The Kidney and Urinary Pathway Knowledge Base' [8], and the 'Human Urinary Proteome Fingerprint Database' to identify proteomic data that might produce CKD biomarker candidates [9][10][11]. The authors identified 114 manuscripts in their literature mining that fit inclusion criteria.…”
Section: Programmatic Efforts To Identify Ckd Biomarkersmentioning
confidence: 99%